Antibiotics for asthma attacks: masking uncertainty. Issue 1 (1st July 2021) - Ramakrishnan, Sanjay; Couillard, Simon
The role for antibiotics in acute asthma has been historically overestimated [1]. From a mechanistic point of view, multiplex PCR testing and conventional microbiological techniques show that >50–80% of events are associated with viral infections, and less than 20% associated with evidence of bacterial infection, with the remaining proportion presumed to be due to allergies and irritants [2]. Consequently, antibiotics are not expected to work in the context of most asthma attacks and their routine use is not recommended. This stance is supported by a Cochrane review, which found inconsistent data to support antimicrobial use [3] and a good quality retrospective cohort study, which associated the combination of antibiotics and oral corticosteroids (OCS) with a longer hospital length of stay, higher hospital cost, and similar risk of treatment failure compared to matched patients treated only with OCS alone [4]. Despite current guidelines advising against, GPs commonly prescribe antibiotics with steroids for asthma attacks. The uncertainty caused by a symptom-based management paradigm probably drives this. A biology-guided management paradigm is needed. https://bit.ly/3iS3CCd